Webinar: A guide to developing quantitative tools for measuring gender norms in agrifood systems - Seymour, Greg; Cole, Steven M.; Costenbader, Elizabeth; Mwakanyamale, Devis; Adeyeye, Olajumoke; Feleke, Shiferaw; Ferguson, Nathaniel; Heckert, Jessica (CGIAR GENDER Impact Platform, 2024)
This Guide is intended for researchers and practitioners who wish to better understand and transform gender norms as the root cause of gender inequalities and women’s disempowerment in agrifood systems. It builds on existing resources that provide guidance on how to measure social norms and gender transformative change in AFSs. The Guide was developed through a collaborative process that started in November 2022 and remains ongoing. Local stakeholders and AFS experts working in Tanzania and Nigeria helped develop the Guide with researchers from the following institutions: International Food Policy Research Institute (IFPRI), International Institute of Tropical Agriculture (IITA), FHI360 & KIT Royal Tropical Institute. A survey was developed using the Guide and was piloted within the cassava, poultry, and fisheries AFSs in Tanzania and Nigeria.